ESTIMATION OF THE ELECTRODYNAMICAL FORCES NEAR FERROMAGNETIC COMPONENTS LOCATED INSIDE LOW VOLTAGE SWITCHING DEVICES - Flaviu Mihai FRIGURA-ILIASA; SORIN MUȘUROI; Petru ANDEA; Mihaela FRIGURA-ILIASA (Annals: Series on engineering sciences (Academy of Romanian Scientists), 2018)
Inside power apparatus, electric conductors are often placed nearby ferromagnetic walls or inside ferromagnetic slots. It is important to know exactly the forces which appear in those situations, in order to ensure an adequate design of all machines, apparatus and power equipment. This paper presents a more generalized method to compute these forces, based on Maxwell’s tensors, and taking into consideration the asymmetry of the conductor placement inside a rectangular slot.